Solvothermal synthesized N–S doped carbon dots derived from cavendish banana peel (Musa paradisiaca) for detection of Fe(III) and Pb(II) - Hamid, Muhammadin; Humaidi, Syahrul; Wijoyo, Hadi; Isnaeni, Isnaeni; Saragi, Indah Revita; Simanjuntak, Crystina; Kaus, Noor Haida Mohd; Kechik, M.M.A.; Nurbillah, Agus; Yaakob, Yazid; Nasution, Tulus Ikhsan (Elsevier BV, 2024)
The synthesis of NS-CDs was carried out using precursors from Cavendish Banana Peel and L-Cysteine as a dopant with the solvothermal method. The characteristics of NS-CDs were analyzed through High-resolution transmission electron microscopy (HR-TEM), X-ray diffractometer (XRD), energy dispersive X-Ray spectroscopy (EDX), X-Ray Fluorescence spectrometer (XRF), X-Ray photoelectron spectroscopy (XPS), UV–Visible spectrophotometer, Photoluminescence, and Atomic Absorption Spectroscopy (AAS). Based on HR-TEM analysis, NS-CDs exhibited a spherical shape (dot) with an average particle size of 2.03 nm. Meanwhile, based on XRD characterization, NS-CDs showed a graphite carbon shape according to the diffraction patterns (002) and (001). Subsequently, XRF and EDX testing revealed that the elemental composition was dominated by carbon (C), nitrogen (N), Sulphur (S), and oxygen (O). Furthermore, in XPS testing, S2p, C1s, N1s, and O1s peaks correlated around 64 eV, 285 eV, 400 eV, and 531 eV respectively. In UV–Vis testing, the energy gap was found to be 5.71 eV (NS-CDs 3:1), 5.46 eV (NS-CDs 3:1), 5.25 eV (NS-CDs 1:1), 5.51 eV (NS-CDs 1:2), and 5.56 eV (NS-CDs 1:3). Characterization of PL for NS-CDs 3:1, 2:1, 1:1, 1:2, 1:3 showed peak excitation at 403 nm and emission at 493.39 nm, 493.65 nm, 494.98 nm, 496.04 nm, and 497.11 nm, respectively. During heavy metal ion detection testing, Fe(III) and Pb(II) using AAS instruments, it was found that the NS-CDs 1:3 sample yielded the best results with an Adsorption capacity worth 21.35 mg/L and Removal Efficiency worth 85.40 %. These results clearly indicate that NS-CDs material can be used as an ideal heavy metal detection material, especially in wastewater.